1998
DOI: 10.1080/00343409850119418
|View full text |Cite
|
Sign up to set email alerts
|

Do Asymmetric Networks Help or Hinder Small Firms' Ability to Export?

Abstract: ECHEVERRI-CARROLL E., H UNNICUTT L., and HANSEN N. (1998) Do asymmetric networks help or hinder small firms' ability to export?, Reg. Studies 32, 721-733. Studies of industrial districts in Europe and the US and of networked firms in Japan recognize the positive correlation between symmetric networks - those between firms of similar size - and their success in international markets. This relationship is not obvious in the case of asymmetric networks - those between firms of relatively different sizes. The mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…As already noted, Echeverri-Carroll and Hunnicutt (1998) argue that for a sample of high technology firms in Texas, knowledge used to produce innovations came mainly from cities outside the region where the firms were located. We use the notion of dynamic externalities here to mean that regions accumulate different levels of knowledge over time, and interregional knowledge 9 spillovers between regions may be more dependent on technological similarity than geographical proximity.…”
Section: Dynamic Externalitiesmentioning
confidence: 83%
“…As already noted, Echeverri-Carroll and Hunnicutt (1998) argue that for a sample of high technology firms in Texas, knowledge used to produce innovations came mainly from cities outside the region where the firms were located. We use the notion of dynamic externalities here to mean that regions accumulate different levels of knowledge over time, and interregional knowledge 9 spillovers between regions may be more dependent on technological similarity than geographical proximity.…”
Section: Dynamic Externalitiesmentioning
confidence: 83%
“…In a study of high-technology rms in Texas, Echeverri-Carroll et al (1998) concluded that investor linkages had provided suf cient information and resources to smaller suppliers to undertake independent international expansion. Long-term relationships can lead to steady improvements in their production processes, often as a result of investor support to achieve higher-quality production and distribution standards and lower-defect rates.…”
Section: Foreign Investment and The Internationalization Of Local Supmentioning
confidence: 99%
“…Further, the recent process of production fragmentation and the rapid growth of firm clusters have been explained by the increasing need for output flexibility (Propris 2001). The recent literature has focused on cluster approach for suppliers (Echeverri-carroll et al 1998, Belussi 1999, Hemmert 1999, Porter 2000, Propris 2001). The literature on the cluster approach of suppliers has identified one of the factors which can be the source for suppliers' output flexibility, i.e.…”
Section: Background and Motivationmentioning
confidence: 99%